1986
DOI: 10.1007/bf00046234
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptides in free-living and parasitic flatworms (Platyhelminthes). An immunocytochemical study

Abstract: The nervous systems of the turbellarians Microstomum lineare and Polycelis nigra and of the cestodes Diphyllobothrium dendriticum and Schistocephalus solidus were studied by means of the peroxidaseantiperoxidase (PAP) immunocytochemical method, with the use of antisera to the neuropeptides FMRFamide, vasotocin, leu-enkephalin, met-enkephalin, neurotensin, somatostatin, and VIP, and to the bioamine serotonin. Anti-FMRF-amide positive perikarya and fibers occurred in all species, while the occurrence of the vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…IR to these substances is obtained in all investigated species. Previous studies have revealed anti-FMRF-amide IR in the following flatworm taxa: Catenulida (Wikgren and Reuter 1985), Macrostomida (Reuter et al 1984, 1986, Tricladida (Wikgren et al 1986), Monogenea (Reuter 1987), Digenea (Gustafsson 1987) and Cestoda (Gustafsson et al 1985). The additional findings of FMRF-amide-like IR in the Rhabdocoela, the Proseriata and the Acoela and its occurrence in Coelenterata (Grimmelikhuijzen 1984) support the status of this peptide family as symplesiomorphic in the Platyhelminthes (Wikgren and Reuter 1985) and the substances as ancestral, evolutionarily relatively stable, neuroregulating substances of crucial importance in primitive nervous systems (Grimmelikhuijzen 1983).…”
Section: Evidence Of Neuroactive Substances In Flatworms 33mentioning
confidence: 97%
See 4 more Smart Citations
“…IR to these substances is obtained in all investigated species. Previous studies have revealed anti-FMRF-amide IR in the following flatworm taxa: Catenulida (Wikgren and Reuter 1985), Macrostomida (Reuter et al 1984, 1986, Tricladida (Wikgren et al 1986), Monogenea (Reuter 1987), Digenea (Gustafsson 1987) and Cestoda (Gustafsson et al 1985). The additional findings of FMRF-amide-like IR in the Rhabdocoela, the Proseriata and the Acoela and its occurrence in Coelenterata (Grimmelikhuijzen 1984) support the status of this peptide family as symplesiomorphic in the Platyhelminthes (Wikgren and Reuter 1985) and the substances as ancestral, evolutionarily relatively stable, neuroregulating substances of crucial importance in primitive nervous systems (Grimmelikhuijzen 1983).…”
Section: Evidence Of Neuroactive Substances In Flatworms 33mentioning
confidence: 97%
“…In addition, IR to bovine pancreatic polypeptide (BPP) and to vasotocin antisera has been reported for this flatworm (Wikgren et al 1986, Reuter andPalmberg 1987). In planarians IR has been demonstrated to FMRF-amide, 5-HT, leu-enkephalin, met-enkephahn, neurotensin, somatostatin, ACTH and neurophysin antisera (Schilt et al 1981, Carraway et al 1982, Kerschbaum et al 1984, Wikgren et al 1986). In the monogenean species Gyrodactylus salaris IR has been obtained to anti-5-HT, anti-FMRF-amide, anti-GRF, anti-leu-enkephalin and anti-urotensin I (Reuter 1987).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations